2001
DOI: 10.1149/1.1377898
|View full text |Cite
|
Sign up to set email alerts
|

Three-Additive Model of Superfilling of Copper

Abstract: A model describing the effect of an accelerator bis(3-sulfopropyl)disulfide (SPS) and the two inhibitors poly(ethylene glycol) and Janus Green B (PEG and JGB) on the leveling efficacy on submicrometer trenches of an acid-copper plating bath is described, simulated, and compared to experimental fill studies. All parameters of the model are estimated from electrochemical measurements on a nonpatterned, rotating disk electrode. A multicomponent version of a Frumkin isotherm is employed to account for the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
143
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 14 publications
(26 reference statements)
0
143
0
1
Order By: Relevance
“…Two factors confirmed that SPS was adsorbed at the bottom of the trenches; (1) low adsorption density of L2, because of the negligible convection and (2) low concentration of S2 with a lower diffusion coefficient compared to Cu 2+ or SPS. 34,35 SPS was also accumulated at the bottom-corner of the trenches in the stationary condition, forming a rounded growing surface until 10 min of filling time. The co-adsorption of S2 and L2 severely suppressed Cu deposition at the top and lateral wall where the strong convective flow was applied.…”
Section: Resultsmentioning
confidence: 99%
“…Two factors confirmed that SPS was adsorbed at the bottom of the trenches; (1) low adsorption density of L2, because of the negligible convection and (2) low concentration of S2 with a lower diffusion coefficient compared to Cu 2+ or SPS. 34,35 SPS was also accumulated at the bottom-corner of the trenches in the stationary condition, forming a rounded growing surface until 10 min of filling time. The co-adsorption of S2 and L2 severely suppressed Cu deposition at the top and lateral wall where the strong convective flow was applied.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] They can be divided into two types. In one type, the additive has a promotional effect on copper deposition and it is concentrated in the bottom of the trench.…”
Section: Filling Modelmentioning
confidence: 99%
“…In the electronics and electrical industries, additives can include suppressors, accelerators and levellers to produce desirable coatings. 6 Common examples include polypropylene glycol, [7][8][9] bis(3-sulphopropyl) disulphide, nitrogen containing aromatic compounds, 10,11 thiourea, 12 gelatine, 13 3-mercapto-1-propanesulphonate 14,15 and chloride ion. 16 Such chemicals are added in small quantities and can realise an improved deposit quality involving the appearance of the plated metal (surface brightness), a modified coating structure together with physical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%